Pengaruh Penggunaan Media Pembelajaran Berbasis WEB digital Linktree Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Informatika Kelas X SMK Negeri 2 Bone - Andi Muh Rezky; Syarif Nur; A. Suharman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the implementation of Linktree-based digital web learning media and its effect on students’ learning outcomes in Informatics for grade X students at SMK Negeri 2 Bone. The study employed a quantitative approach using a nonequivalent control group design. The research was conducted at SMK Negeri 2 Bone from September to October 2024. The sample consisted of an experimental class and a control class. Data were collected through observation, tests, and documentation. The data were analyzed descriptively and inferentially using a normality test and paired sample t-test. The findings indicated that the implementation of Linktree-based learning media was carried out through preliminary, core, and closing stages, and encouraged students’ enthusiasm during the learning process. The experimental group’s mean pretest score was 47.73 and increased to 76.82 in the posttest, while the control group only increased from 40.45 to 44.55. Hypothesis testing showed that t-count = 8.223 > t-table = 2.074 with a significance value of 0.000 < 0.05, indicating that the use of Linktree-based digital web learning media had a significant effect on students’ learning outcomes in Informatics for grade X students at SMK Negeri 2 Bone.